تكلّم اللغة العربيّة (دراسة شبه تجريبية لتلاميذ الصف الحادى عشر فى المدرسة الثانوية الإسلامية الحكومية الأولى بباندونج السنة الدراسية 2013/2014عام) رسالة - Nurhema, - (2014)
Kemampuan berbicara merupakan kemampuan yang sangat penting dalam mempelajari bahasa Arab, karena secara umum kemampuan berbicara bertujuan agar para pelajar mampu berkomunikasi lisan secara baik dan benar. Namun pada kenyataannya kemampuan berbicara bahasa Arab siswa di MAN 1 Kota Bandung masih rendah, padahal kemampuan berbicara bahasa Arab sangat diperlukan. Oleh sebab itu, untuk meningkatkan kemampuan berbicara maka diperlukan sebuah metode pembelajaran yang memudahkan siswa menguasai kemampuan tersebut. Salah satumetodepembelajaran yang digunakandalammeningkatkankemampuanberbicaraadalahmetodeeklektik.Metodeeklektikbisadiartikanmetodegabungan.Dalampenelitianinipenelitimenggabungkanmetodelangsungdankaidah-tarjamah.Penelitianinimenggunakanmetode quasi-eksperimen, dengandesainNon -Equivalent Control Group Design.Populasidalampenelitianiniadalahseluruhsiswakelas XI MAN 1 kota Bandung tahunajaran 2013/2014. Adapunsampeldalampenelitianiniadalahpenelitimemilihkelas XI IPA B sebagaikelompokeksperimendankelas XI Agama sebagaikelompokkontrol. Selanjutnyakelompokeksperimendikenaiperlakuanberupapenggunaanmetodeeklektik, sementarakelompokkontroltidakmenerimaperlakuan yang sama. Instrument penelitian yang digunakanadalah instrument tesdanlembarobservasi.Hasildaripenelitianinimenunjukanbahwa Ho ditolakdan Ha diterima, yaituberartiadanyaefektivitaspenggunaanmetodeeklektikterhadapmeningkatkankemampuanberbicarabahasa Arab siswa. The ability to speak is a very important capability in learning Arabic, because generally speaking skills intended that the students are able to communicate well verbally and correctly. But in fact the ability to speak Arabic MAN 1 students in Bandung is still low, but the ability to speak Arabic is very necessary. Therefore, to improve the ability to speak it would require a method of learning that allows students to master those skills. One of the methods used to improve the ability to speak is an eclectic method. Eclectic method can be interpreted combination method. In this research, researchers combined direct method and grammatical-translationmethod. This research used a quasi-experimental methods, with design Non -Equivalent Control Group Design. The population in this study were all students of class XI MAN 1 Bandung academic year 2013/2014. The sample in this research was a class XI Science researchers B chose as the experimental group and class XI Religion as a control group. Furthermore, the experimental group subjected to treatment that is eclectic method, while the control group did not receive the same treatment. Research instrument used was a test instrument and observation sheets. The results of this study indicate that Ho is rejected and Ha is accepted, that is to say the existence of the Effectiveness of the use of an eclectic method increases students' ability to speak Arabic.